MENINGKATKAN KEDISIPLINAN DAN HASIL BELAJAR PESERTA DIDIK KELAS VB SD KANISIUS KADIROJO PADA MATERI VOLUME BANGUN RUANG MENGGUNAKAN MODEL PROBLEM BASED LEARNING (PBL) - Lina Septiyani; Ignatia Esti Sumarah; Andrias Yance Eko Sutopo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The aim of the research is to improve student discipline and learning outcomes in Mathematics class V B at Kanisius Kadirojo Elementary School. The research carried out was classroom action research using the Problem Based Learning model. Discipline data collection techniques use disciplinary observation sheets, while learning outcomes use evaluation scores. The analysis technique is qualitative descriptive analysis, namely quantitative descriptive by looking for the average value and percentage of learning completeness. The research results show that the application of the Problem Based Learning model improves students' discipline and learning outcomes. Students who passed the KKM were 57.89 in cycle I meeting 1, 84.21% in cycle 1 meeting 2, and 100% in cycle II) and the discipline of students who were in the discipline or very discipline category (66.65% in cycle I meeting 1, 84.2% in cycle II meeting 2 and 94.73% in cycle II). Keywords: Learning Outcomes, Problem Based Learning, Mathematics